(untitled) (International Journal on Stereo & Immersive Media, 2025)
The following piece focuses on how the inclusion of fictional elements into documentaries allows for a different relationship with the film, allowing creators to explore different narrative avenues, characters to relate in a different way to the events and for the audience to actively engage with the film. I rely on two of my previous short documentary films and my current research as examples where I have used fiction inside the documentary form, and I examine how the insertion of fiction into the narrative, allows for a different perspective of the events depicted on each film. My research centers on the relationship between roots, identity and belonging, explored through documentary film. I use the notions of affect, embodied memory, and relationality together with Bergson’s understanding of time and memory to explore my own family’s story and its voids through a documentary film.